The Effect of Job Satisfaction and Individual Characteristics on Turnover Intention in Employees of Ninja Xpress Baturaja Branch - Priharti, Rr Dimas Veronica; Sepiyani, Sindi (Jurnal Indonesia Sosial Sains, 2025)
This study examines the effect of Job Satisfaction and Individual Characteristics on Turnover Intention among employees of Ninja Xpress Baturaja Branch. The population in this study consists of 32 respondents. The analytical method used is quantitative, employing multiple linear regression analysis, which includes validity and reliability tests, as well as t-tests and F-tests. The results of the partial tests (t-test) show that Job Satisfaction significantly affects Turnover Intention, as indicated by a t-value of 15.759, which is greater than the t-table value of 2.045, with a significance value of 0.000 < alpha 0.05. Individual Characteristics also significantly affect Turnover Intention, as indicated by a t-value of 6.817, which is greater than the t-table value of 2.045, with a significance value of 0.000 < alpha 0.05. The simultaneous test (F-test) shows that Job Satisfaction and Individual Characteristics significantly affect Turnover Intention, as indicated by an F-value of 1221.304, which is greater than the F-table value of 3.33, with a significance value of 0.000 < alpha 0.05. Therefore, it can be concluded that the hypothesis stating that Job Satisfaction and Individual Characteristics significantly affect Turnover Intention among employees of Ninja Xpress Baturaja Branch is accepted.